Thermal Runaway and Fire Suppression Applications for Different Types of Lithium Ion Batteries - Cagri Un; Kadir Aydın (Vehicles, 2021)
With the improvement of lithium-ion battery (LIB) technology, safety is becoming increasingly urgent topic for battery electric vehicles (BEVs). Short circuits, overcharging, high temperatures and overheating can cause thermal runaway reactions and the release of the flammable electrolyte which makes fire suppression very difficult. This study focuses on the mechanism of thermal runaway and fire suppression applications of LIBs. In order to understand this, 10 experiments were carried out. The experiments were divided into as Exp. A and Exp. B. A manual water suppression system was used in Exp. A and an automatic boron-based suppression system (AUT-BOR) was used in Exp. B. LIBs were heated in a controlled manner with a heat source and the effects of thermal runaway and fire suppression were observed. In Exp. A, a large amount of water was required to extinguish the LIB fires. The holes and slits which formed in the LIB after a fire were useful for injecting water. A projectile effect of cylindrical cells was observed in Exp. A. The Exp. B results showed that AUT-BOR mitigates risks effectively and safely. Also, AUT-BOR provides an early fire warning system and spot cooling to prevent thermal runaway reactions while localizing and suppressing the fire. In Exp. B, fire detection and suppression occurred without any explosion.